Oxidation of L-Ascorbic Acid in Copper(II) Ion - Catalyzed Polyvinylpyrrolidone Solutions - (:unkn) unknown (SPRINGER, 2009)
The effects of Cu (II) ion and polyvinylpyrrolidone (PVP) (K-30) concentrations on the oxidation kinetics of ascorbic acid (Vitamin C: H,A) in aerated and acetate buffered solution (pH = 4.5) have been investigated at 25 degrees C. The study was carried out in the concentration range of PVP between 0.2% and 0.6%, and in the concentration range of Cu (II) between 0.785 and 3.14 x 10(-7) M. The initial concentrations of H(2)A were 2.8-11.3 x 10(-5) M. The changes in H(2)A concentrations during the reactions were determined from absorbance measurements at a wavelength of 264.0 nm, using direct UV spectrophotometric method. Molecular weight (MW) of the PVP has been redetermined as a mean MW, using viscosimetric method. The rate equation of the Cu (II) ion - catalyzed reaction was found to be first order with respect to H(2)A. The oxidation rate constant decreased with increasing PVP amount for a fixed Cu (II) ion concentration, whereas it. increased with increasing Cu (II) ion concentration for a fixed PVP level. It also increased with increasing concentration of H(2)A for a fixed Cu (II) ion concentration.
Keywords: Ascorbic acid; copper (II)-catalyzed oxidation; kinetic-spectrophotometric method; polyvinylpyrrolidone; DIRECT ULTRAVIOLET SPECTROPHOTOMETRY; BACKGROUND CORRECTION; MOLECULAR OXYGEN; FRUIT JUICES; SOFT DRINKS; METAL ION; KINETICS; AUTOXIDATION